Development and validation of an LC–MS/MS quantitative method for endogenous deoxynucleoside triphosphates in cellular lysate. (21st September 2016) - Chen, Xinhui; McAllister, Kevin J.; Klein, Brandon; Bushman, Lane R.; Anderson, Peter L.
Abstract: The endogenous deoxynucleoside triphosphate (dNTP) pool includes deoxyadenosine triphosphate (dATP), deoxycytidine triphosphate (dCTP), deoxyguanosine triphosphate (dGTP) and thymidine triphosphate (TTP). The endogenous dNTP pool is regulated by complex enzymatic pathways that can be targeted by drugs, such as antimetabolites. In addition, these components compete with antiviral nucleos(t)ide analog triphosphates, contributing to the mechanism of pharmacologic action. This communication describes the development and validation of a sensitive method to quantify the intracellular dNTP pool in cellular lysates. The extraction process was optimized for dNTPs using an indirect strategy – the separation of mono‐, di‐ and triphosphate moieties by strong anion exchange, dephosphorylation of target fractions to molar equivalent nucleosides – followed by sensitive quantitation using liquid chromatography–tandem mass spectrometry. The validated analytical range was 50–2500 fmol/sample for each dNTP. The assay was used to quantify dNTPs in peripheral blood mononuclear cells from 40 clinical research participants ( n =  279 samples). Median (interquartile range) concentrations were 143 (116, 169) for dATP, 737 (605, 887) for dCTP, 237 (200, 290) for dGTP and 315 (220, 456) for TTP, in femtomoles per million cells. This method allows for future studies of endogenous dNTP disposition in subjects receiving antimetabolites or nucleos(t)ide analogs, or for other clinical scenarios.